Learning Figurative Language through Taylor Swift’s ‘Willow”: A Genre-Based and Multimodal Framework for Secondary ELT - Kurniawan, Jesselyn Fernanda Vereen; Palangan, Barans Irawan (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
Learning figurative language remains a complex yet important aspect of English language education. It often challenges students due to its abstract nature and cultural depth. The purpose of this study is to investigate how Taylor Swift’s Willow and its music video can be integrated as multimodal materials for teaching figurative language through the six English language skills: listening, speaking, reading, writing, viewing, and representing. Using a qualitative method based on literature analysis, the study develops a structured lesson plan grounded in the Genre-Based Approach (GBA) and aligned with Sustainable Development Goals (SDGs). This study identifies that Willow contains rich figurative elements such as simile, metaphor, personification, hyperbole, and symbolism. These elements not only enhance linguistic understanding but also provide cultural and emotional depth. The music video further supports comprehension by giving symbolic visual cues, making abstract meanings more understandable for learners. The lesson plan outlines three meetings, each focusing on different skill pairs while embedding the five stages of GBA. The study highlights that incorporating Willow as a multimodal learning resource supports students’ critical and creative thinking, improves cultural understanding, and increases engagement. It is a relatable and effective method for teaching figurative language in modern English classrooms.Keywords: figurative language, multimodal learning, Taylor Swift, lesson plan, GBA